Administrasi Sarana dan Prasarana Pendidikan - Fiddini Izaturahmi; Putri Adillah; Yova Murnika; Shafiah Shafiah; Sakban Sakban (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
In this article, the author will elaborate on the governance of facilities and infrastructure within the school environment. The management of facilities and infrastructure emerges as a crucial aspect in the realm of education. Every activity within the school necessitates facilities and infrastructure, directly or indirectly, to support the smooth progress of the learning process. The significance of managing facilities and infrastructure significantly contributes to the achievement of educational objectives. The educational environment can be influenced both positively and negatively by the maintenance of school facilities and infrastructure. Effective management of infrastructure serves as the key to success, although there are still some areas that have not been fully optimized. Therefore, the author compiles this article with the hope that it can serve as a crucial reference in the administration of facilities and infrastructure in the educational context.